Globally Networked Learning in a University Classroom: A Pilot Program - Steven M. Oberhelman; Christina A. Dunn (Athens Institute for Education and Research, 2019)
In 2017, the College of Liberal Arts at Texas A&M University created an initiative modeled on the State University of New York's Collaborative Online International Learning (COIL) program. COIL is an approach to fostering global competence through the development of a multicultural learning environment that links university classes in two different countries. Using various communication technologies, students complete shared assignments and projects, with faculty members from each country co-teaching and managing coursework. We piloted a COIL program with the purpose of fostering global competence and a multicultural learning environment through linking a Texas A&M Liberal Arts class and a university class in a foreign country. Each of the paired classes met separately and regularly in its home country for much of the semester, but the students also worked asynchronously online to share ideas, collaboratively produce work relevant to the course of study, and reflect upon their own and their partners' cultural points of view. In this paper we discuss the results of this pilot program.